PEMETAAN TENTANG PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN PRODUKTIF AKUNTANSI KELAS X AKUNTANSI DI SMK NEGERI 2 BUDURAN SIDOARJO - APRILIA EKA SUGIANTO (Jurnal Pendidikan Akuntansi (JPAK), 2013)
A country for moving towards a better, requires education plays an important role in the formation of character and personality of the nation. But one of the problems that faced by Indonesia is the low quality of education in Indonesia. The factor that caused the problem is unapportionment education standardization, one of it is apportionment infrastructure in this case is a taching media. The research kind is descriptive research with quantitative approach. The data collection methode use documentation, interview, and questionare. The result analysis will be calculated using the Likert scale. Based on the analysis and calculation of teaching media feasibility like a language feasibility, presentation feasibility, and content feasibility, teaching media that are used by teacher on learning process is feasible. The results of the feasibility study of media supported by the results of the calculation and analysis student response with result is feasible. So, it can be conclused if the teaching media that are used by teacher on accounting productive lesson in accounting tenth class Buduran Sidoarjo State Vocational High School 2 is feasible as teaching media during learning process. Keywords: Feasibility, Teaching Media